Methodological Principles of the Formation of Cultural Competence of Future Art Teachers According to the Educational and Motivational Criterion - Baranovska, Iryna; Dobrovolska, Rufina; Yakymenko, Yulia (Educological discourse, 2024)
The article raised the issue and considered different views of modern scientists on the problem of forming cultural competence of future teachers of art disciplines. Normative educational documents and scientific work of modern scientists in the field of art pedagogy on the research problem were analyzed. The conceptual role of art for the formation of cultural immunity and cultural intelligence of the individual is determined. The position regarding the choice of an educational vector in the formation of cultural competence of future art teachers is substantiated. The essence of the phenomenon "cultural competence" is characterized and its motivational-educational, cognitive-communicative, innovation-discursive structural components are determined. The scientific approaches of semiotic-hermeneutic, creative-communicative, innovative-reflexive and the principles of their implementation are substantiated: integration of knowledge and skills acquired in the process of mastering the content of the curriculum disciplines, actualization of one's own educational experience, activation of artistic and associative imagination and personified penetration into the artist's artistic vision , pedagogical tolerance, pedagogical artistry, pedagogical support of the interpretive and methodical initiative of future teachers of art disciplines and orientation to the application of innovative artistic technologies in the educational process. The results of a diagnostic study of the levels of formation of the cultural competence of the applicants according to the motivational and educational criterion are presented. Prospects for further research are defined as the development of special diagnostic tasks and the selection of diagnostic methods for determining the levels of all indicators of the studied construct and the development of methods for forming the communicative competence of future art teachers by means of innovative technologies.